Loss-framing of information and pre-vaccination consultation improve COVID-19 vaccine acceptance: A survey experiment - Wang, Kailu; Wong, Eliza Lai-Yi; Cheung, Annie Wai-Ling; Dong, Dong; Yeoh, Eng-Kiong (Frontiers in Public Health, 2023)
Backgrounds: Vaccination remains one of the most effective ways to protect populations from COVID-19 infection, severe conditions, and death. This study aims to examine whether the gain/loss-framing of information, provision of subsidized pre-vaccination physician consultation, and cash incentives can improve COVID-19 acceptance amongst adults. Methods: A survey experiment was conducted within a broader cross-sectional survey of people aged 18-64 years in Hong Kong, China. The participants were randomly assigned to one of the eight groups derived from full-factorial design of the three strategies with stratification by age and sex. The vaccine acceptance rate was compared between people with and without any of the strategies. The heterogeneous effects of these strategies were identified for those with different perceptions of the pandemics and vaccine in multiple logistic regressions. Results: The survey experiment collected 1,000 valid responses. It found that loss-framed information and provision of subsidized physician consultation to assess suitability to be vaccinated, can improve vaccine acceptance, while cash incentives did not make a difference. The improvement effect of loss-framing information and physician consultation is stronger among those with higher perceived infection risk and severity of condition, as well as unvaccinated people with lower confidence in vaccine safety. Conclusions: The findings indicated that individualized loss-framing messages and equitable provision of subsidized pre-vaccination physician consultations can be incorporated in efforts to promote vaccine acceptance and vaccination roll-out speed. However, it remains inconclusive whether and how universal cash incentives may be deployed to support vaccination promotion.